Socialization, Selection, or Both? The Role of Gene-Environment Interplay in the Association Between Exposure to Antisocial Peers and Delinquency - Schwartz, Joseph A. (Journal of quantitative criminology, 2019)
To better explain the near-universal association between peer and self-reported delinquency, three frameworks have been offered and have received varying degrees of support: socialization or the social transmission of norms, attitudes, and behaviors among group members; selection or the congregation of youth with similar traits and predispositions; and enhancement or a combination of socialization and selection processes.